2018
DOI: 10.1080/07420528.2017.1420078
|View full text |Cite
|
Sign up to set email alerts
|

Premature birth and circadian preference in young adulthood: evidence from two birth cohorts

Abstract: A preference for eveningness (being a "night owl") and preterm birth (<37 weeks of gestation) are associated with similar adversities, such as elevated blood pressure, impaired glucose regulation, poorer physical fitness, and lower mood. Yet, it remains unclear if and how preterm birth is associated with circadian preference. The aim of this study was to assess this association across the whole gestation range, using both objective and subjective measurements of circadian preference. Circadian preference was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Two studies found no differences in most macrosleep architecture variables including bedtime, get up time, total sleep duration, nocturnal wakefulness, sleep midpoint, and circadian preference between preterm and full-term children at age 2 years 42 and in early adulthood. 34 However, in another study of 5- to 12-year-olds that used polysomnography to measure and compare sleep in preterm children with fetal growth restrictions, preterm children with appropriate birth weight for gestational age, and full-term children, the preterm children with appropriate birth weight for their gestational age had a significant decrease in total sleep duration, sleep efficiency, and nonrapid eye movement sleep and a significant increase in wake after sleep onset compared with the other 2 groups. 31 This study also investigated microsleep architecture and found that preterm children had altered microarchitecture compared with full-term children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found no differences in most macrosleep architecture variables including bedtime, get up time, total sleep duration, nocturnal wakefulness, sleep midpoint, and circadian preference between preterm and full-term children at age 2 years 42 and in early adulthood. 34 However, in another study of 5- to 12-year-olds that used polysomnography to measure and compare sleep in preterm children with fetal growth restrictions, preterm children with appropriate birth weight for gestational age, and full-term children, the preterm children with appropriate birth weight for their gestational age had a significant decrease in total sleep duration, sleep efficiency, and nonrapid eye movement sleep and a significant increase in wake after sleep onset compared with the other 2 groups. 31 This study also investigated microsleep architecture and found that preterm children had altered microarchitecture compared with full-term children.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies explicitly reported a population-based participant recruitment. 16,[32][33][34][35][36][37][38][39] The follow-up frequency ranged from 1 to 6 times, with the earliest postnatal follow-up started from 10 days after birth 40 and the longest follow-up happened at 24 years of the children's age. 34 Regarding study quality appraisal, 96.67% of included studies (29/ 30) had the Newcastle-Ottawa Scale score ranging from 6 to 8, indicating moderate to high quality.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of the 2,193 individuals in the AYLS cohort, 1,913 were invited and 1,136 (51.8% of original cohort) took part in a clinical examination between 2009 and 2012. As in previous ESTER‐AYLS publications (Bjorkqvist et al., ; Matinolli et al., ), we included as term controls only individuals from the group not admitted to neonatal ward (see Study design above), because the admitted group represents a range of prenatal and neonatal adversities not representative of those born at term. Length of gestation was confirmed from medical records for 489 individuals who gave their permission; 46 were born early preterm, 129 late preterm and 314 were born at term.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Studies of fetal or infant determinants of 24-h activity rhythms in childhood are scarce. Findings from two Finnish actigraphy studies among young adults born preterm and full-term suggest that very low birth weight children might show an earlier chronotype in adult life (Björkqvist et al, 2018(Björkqvist et al, , 2020. Possible mechanisms include a longer period of melatonin deficiency after birth and adverse effects on circadian rhythm programming by prenatal hypoxia, and protein malnutrition and environmental factors in the early postnatal period (Björkqvist et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from two Finnish actigraphy studies among young adults born preterm and full-term suggest that very low birth weight children might show an earlier chronotype in adult life (Björkqvist et al, 2018(Björkqvist et al, , 2020. Possible mechanisms include a longer period of melatonin deficiency after birth and adverse effects on circadian rhythm programming by prenatal hypoxia, and protein malnutrition and environmental factors in the early postnatal period (Björkqvist et al, 2018). The age of onset of developing the suggested earlier chronotype, as well as its relationship with cardiometabolic health, require further investigation.…”
Section: Introductionmentioning
confidence: 99%